Age-differential sexual dimorphisms in CHD8-S62X-mutant mouse synapses and transcriptomes - Soo Yeon Lee; Hanseul Kweon; Hyojin Kang; Eunjoon Kim; Eunjoon Kim (Frontiers in Molecular Neuroscience, 2023)
Chd8+/N2373K mice with a human C-terminal-truncating mutation (N2373K) display autistic-like behaviors in juvenile and adult males but not in females. In contrast, Chd8+/S62X mice with a human N-terminal-truncating mutation (S62X) display behavioral deficits in juvenile males (not females) and adult males and females, indicative of age-differential sexually dimorphic behaviors. Excitatory synaptic transmission is suppressed and enhanced in male and female Chd8+/S62X juveniles, respectively, but similarly enhanced in adult male and female mutants. ASD-like transcriptomic changes are stronger in newborn and juvenile (but not adult) Chd8+/S62X males but in newborn and adult (not juvenile) Chd8+/S62X females. These results point to age-differential sexual dimorphisms in Chd8+/S62X mice at synaptic and transcriptomic levels, in addition to the behavioral level.